CuCo2O4 nanoparticles encapsulated by onion-like carbon layers: A promising solution for high-performance lithium ion battery. Issue 10 (1st August 2016) - Han, Dandan; Hu, He; Liu, Bao; Song, Gengxin; Yan, He; Di, Juan
Abstract: We report an approach of preparing dispersive CuCo2 O4 nanoparticles completely encapsulated by onion-like carbon (OLC) layers. The CuCo2 O4 /OLC nanocapsules are prepared by the arc discharge method and the following air annealed process. As an anode for lithium ion batteries (LIBs), the discharge capacity of this nanocapsules is 743.2 mA h g −1 at a current of 0.2 A g −1 after 300 cycles. The discharge can also retain 539.6 mA h g −1 at a high current of 5.0 A g −1 . The high cycling stability and rate capability result from the nanocapsules combining the advantages of CuCo2 O4 nanoparticles and OLC shells. The CuCo2 O4 nanoparticles provide sufficient contact with the electrolyte and rapid three-dimensional Li + diffusion channels; OLC improves the conductivity and the structural stability of CuCo2 O4 nanoparticles. The CuCo2 O4 /OLC nanocapsules with the high electrochemical performance would have the potential for applications in LIBs with long cycling life and high power density.